주희 철학에서 앎과 실천의 관계에 관한 고찰 ― 진지(眞知)를 중심으로 - 오주연; Oh Juyeon (중국학보, 2025)
이 글은 주희(朱熹) 철학에서 도덕 실천의 동력을 ‘진지(眞知)’ 개념을 중심으로 탐구한다. 주희는 도덕 실천에서 앎의 역할을 강조하며, 격물궁리(格物窮理)를 통해 사태에 적절히 조응하는 능력을 함양할 수 있다고 보았다. 그러나 이러한 앎 중심의 윤리 체계는 ‘앎이 실천을 담보할 수 있는가’라는 문제 제기에 직면해 왔고, 특히 모종삼의 자율성 담론에서 주희 철학은 실천의 필연성이 결여된 이론으로 비판되었다. 이에 대한 대응으로 진지를 실천의 원천으로 제시하는 입장이 등장했으나, 이러한 논의들은 진지를 실천을 추동하는 결정적 계기로 설명하지 못하거나 진지의 의미를 ‘의무에 대한 앎’으로 국한시켜 주희 철학의 실천을 정해진 규율의 이행으로만 간주하게 한다. 본고는 이러한 기존 해석의 한계를 넘어서기 위해, 진지를 소이연(所以然)에 대한 자각을 포함하는 심화된 앎으로 규정하고, 그것이 어떻게 실천을 추동하는지를 밝히고자 한다. 주희는 지행불일치의 문제를 자기(自欺) 개념으로 설명하면서, 얕은 앎[淺知]이 의지박약을 초래한다고 진단하였다. 반면 진지는 당위에 대한 근거를 명징하게 파악한 상태로서, 단지 지향해야 할 가치나 규범이 무엇인지를 아는 데 그치지 않고, 그것을 왜 지향해야 하는지에 대한 투철한 자각을 포함한다. 이러한 앎은 천지와 달리, 소당연에 대한 확신을 불러일으켜 실천을 자연스럽게 추동한다. 이때 실천은 규범의 기계적 준수가 아니라, 자아와 세계의 본질에 대한 통찰에서 비롯된 자발적인 도덕 행위이다. 결론적으로 진지는 주희 철학에서 앎과 실천을 연결하는 핵심 고리이며, 내면화된 규범을 넘어 현실의 구체적 사태에 조화롭게 대응할 수 있는 윤리적 주체의 형성을 가능케 하는 이론적 기반을 제공한다. This paper investigates the concept of Zhenzhi(眞知, true knowledge) as the moral motivational force in the philosophy of Zhu Xi(1130-1200). Zhu emphasized the role of knowledge in moral practice, asserting that one can cultivate the ability to respond appropriately to concrete situations through the practice of gewu qiongli(格物窮理), the investigation of things and the extension of knowledge. However, this knowledge-centered ethical framework has long faced the critical question: Can knowledge guarantee moral action? In particular, Mou Zongsan criticized Zhu’s philosophy for lacking the necessary connection between knowledge and practice. In response, some scholars have conceived of zhenzhi as the source of moral motivation, but such interpretations often either fail to explain how zhenzhi directly motivates action or reduce it to mere knowledge of moral duty, thereby confining Zhu’s ethics to the mechanical fulfillment of normative rules. This paper seeks to go beyond these limitations by redefining zhenzhi as a deepened form of knowledge that includes an awareness of suoyiran(所以然), the underlying reason or ground for moral obligation. According to Zhu, the failure to act upon what one knows―zhixing bu yizhi(知行不一致)―results from ziqi(自欺), or self-deception, which arises from superficial or partial knowledge(qianzhi, 淺知). In contrast, zhenzhi entails not only an understanding of what should be done but also a clear grasp of why it ought to be done. Such knowledge evokes firm conviction and moral confidence, thereby naturally motivating action. In this view, moral practice is not the mechanical adherence to external norms, but rather a spontaneous and creative expression of insight into the essential principles of the self and the world. Zhenzhi, as such, serves as a crucial link between knowledge and action in Zhu Xi’s philosophy. It serves as a theoretical basis for moral agency that goes beyond the internalization of rules and enables a person to respond appropriately and harmoniously to concrete, complex situations.